Optimization of Drying Kinetics and Quality Parameters of Broccoli Florets - Reyes-Salinas, A; Mahn-Osses, A (2011)
Drying kinetics of broccoli florets in a tunnel dryer was studied. Effective moisture diffusivity (Deff) and activation energy for moisture diffusion (E0) were estimated. The effect of air temperature, air flow rate and particle size on antioxidant capacity, greenness and texture were calculated through a 23 factorial design. Air flow rate and temperature significantly affected drying time. Deff fluctuated between 2.82 × 10 -10 and 2.00 × 10-9 (m2/s), and E0 was around 42 KJ/mol, agreeing with values reported in literature. The maximum antioxidant activity was obtained at 60°C, air flow rate of 4 m/s and 1.5 cm particle diameter, resulting in a 70 percent reduction in free radical scavenging ability and a 29 percent increase in total reductive capability. Air temperature had significant effect on greenness, and air flow rate significantly affected texture. The optimization of convective drying of broccoli allows maximizing antioxidant activity and minimizing cost by saving energy and time. © 2011 Berkeley Electronic Press. All rights reserved.